Analysis of academic performance of medical students in studying pharmacology during quarantine and martial law in Ukraine - Lutsenko, Ruslan; Lutsenko, Olga; Vazhnichaya, Elena; Sydorenko, Antonina; Rud, Mariia; Petrenko, Lesia (Frontiers in Education, 2026)
The objective is to analyze the quantitative indicators of academic performance of medical students studied Pharmacology remotely or in a hybrid form of education under the conditions of pandemic and Russian invasion of Ukraine. Regulatory documents related to quarantine due to COVID-19 and martial law in Ukraine, as well as forms of education for 2018–2023, were studied. The quantitative indicators of students' academic performance during the study of Pharmacology Modules 1–2 in Poltava State Medical University were analyzed. The 2018/2019 academic year with face-to-face study (period I) served as a control. The 2019/2020 academic year was characterized by the beginning of quarantine and the transition to distance learning (period II). The next three academic years were spent under conditions of quarantine or its combination with martial law and a hybrid form of education (periods III–V). It is shown that the average current grade of students mastering Pharmacology Module 1 during periods IV and V was higher than in the period I. It exceeded that at the final module control. The final control grade in period IV was higher than in the face-to-face form of education. Mean scores from Module 2 in periods IV and V also were better against control.